The Oral Microbiome: A Silent Contributor to Systemic Health and Disease National Institutes of Health 2024 Workshop - Gabriela Riscuta; Anil Wali; Emmanuel F. Mongodin; Mukesh Verma; Marco Cardone; Hye-Sook Kim; Tamara McNealy; Altaf Mohammed (Cancer Epidemiology, Biomarkers & Prevention, 2026)
Abstract Previously considered primarily only in the context of dental diseases, the oral microbiome is now recognized as a contributor to a variety of systemic diseases, including cancer and cardiovascular diseases. This commentary explores the evolving view of the oral cavity as a gateway to the body’s broader physiologic networks, implicating oral microbiome dysbiosis in a spectrum of chronic conditions. Drawing on current evidence, we propose a re-envisioned healthcare model that integrates oral and systemic health and outline research gaps and clinical priorities to harness the oral microbiome for preventive and therapeutic gains, emphasizing cancer-relevant biomarkers and intervention opportunities.